AN EPQ PRODUCTION-INVENTORY MODEL WITH VARIABLE HOLDING COST - Alfares, Hesham (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
Instantaneous order replenishment and constant holding cost are two fundamental assumptions of the economic order quantity (EOQ) model. This paper presents modifications to both of these basic assumptions. First, non-instantaneous order replenishment is assumed, i.e. a finite production rate of the economic production quantity (EPQ) model is considered. Second, the holding cost per unit per time period is assumed to vary according to the length of the storage duration. Two types of holding cost variability with longer storage times are considered: retroactive increase and incremental increase. For both cases, models are formulated, solutions algorithms are developed, and examples are solved.